Ekpo, Margaret (2020)
Margaret Ekpo was a woman leader, a pioneer parliamentarian and a human rights activist who contributed immensely to the political development of Nigeria during the colonial and pre-Civil War eras. She was actively involved in the struggle for Nigerian independence, and agitations for women’s inclusion in policies and programs of government. A leading member of National Council of Nigeria and Cameroons (NCNC), which became the National Council for Nigerian Citizens in 1960, Margaret rose to become a member of National Executive Council (NEC) of the party as well as the Vice President of the NCNC Women Association. In 1954, she was appointed a Chief with a seat in the Eastern House of Chiefs, breaking gender barrier that had hitherto made the space a male preserve. Margaret was a patriotic Nigerian. As part of her contributions to the constitutional development of Nigeria, Ekpo attended many constitutional conferences in Lagos and London as an adviser to the NCNC. She deployed different strategies to build political consciousness among women in Eastern Region of Nigeria. Her concern on universal suffrage led her to speak unequivocally against women exclusion in political process in the Northern Region of Nigeria. Margaret was an industrialist. She founded a sewing institute named “Windsor Domestic Science Institute” where she trained women in bookkeeping, dressmaking, and home economics among other activities. She believed that women must not be idle but work to earn income to assist their husbands. Margaret founded Aba Market Women Association, which she also used as a platform to educate women on their rights. She was rights activist who utilized her position as a parliamentarian to agitate for the political, economic, educational, and cultural emancipation of her people. For instance, she fought for the welfare of workers and their fundamental human rights. She demanded gender equity in the appointment of people to the Census Board, employment in the police force, and called for more girls to be offered scholarships. Margaret mobilized women against the British colonial administrators following the killing of coal miners at Iva Valley, Enugu, known as “Enugu Colliery Massacre” in 1949, and the murder of Onyia, a wardress in Enugu prison killed in 1954 for her refusal of sexual advances of a warder. She wanted government to coordinate the processes through which Nigerian students abroad access scholarships. Margaret believed in the indivisibility of Nigeria and suffered for her conviction during the Nigeria–Biafra Civil War (1966–1970). For her services to humanity, Ekpo received several awards and honors. An airport, Margaret Ekpo Airport Calabar, was named after her in her life time. She was awarded National Officer of the Order of Niger (NOON) and Commander of the Order of Federal Republic (OFR). Ekpo was a member of the Board of Trustees of Women’s Research and Documentation Centre (WORDOC), Institute of African Studies, University of Ibadan, Ibadan, Nigeria. Chief Margaret Ekpo died on September, 21, 2006 at the age of ninety-two.